Mitogenomic features of Pteronarcys sachalina (Plecoptera: Pteronarcyidae), the only salmonfly known from China - Chen, Zhi-Teng (Zootaxa, 2020)
The complete mitochondrial genome (mitogenome) of Pteronarcys sachalina Klapálek was sequenced and compared with those of two other salmonflies for the first time. The mitogenome of P. sachalina was 16,180 bp in length, with an A+T content of 70.6%. The uniform set of 37 genes (13 PCGs, 22 tRNA genes and two rRNA genes) and a long control region (1431 bp) were all annotated. Most PCGs had standard ATN start codons and TAN stop codons. COX1 exhibited the highest evolutionary rate among the 13 PCGs of sequenced species of Pteronarcyidae. ND2 was truncated at the 3′ end when compared with congeners. Most tRNA genes had typical cloverleaf secondary structures, whereas the dihydrouridine (DHU) arm of trnS1 was reduced. Tandem repeats and stem-loop (SL) structures were predicted in the control region of P. sachalina. Conserved sequences were found in control regions of the three already sequenced salmonflies, P. sachalina, Pteronarcys princeps Banks, and Pteronarcella badia (Hagen).